Four new species of free-living marine nematodes of the family Comesomatidae (Nematoda: Araeolaimida) from coast of Vietnam - Gagarin, Vladimir G. (Zootaxa, 2013)
Specimens of four new nematode species of the family Comesomatidae were isolated from the sediments of littoral zone of South China Sea at the coast of Vietnam and described and illustrated. Sabatieria curvispiculata sp. n. is characterized by the long and slender tail, short cephalic setae and strongly curved spicules in males. Setosabatiera orientalis sp. n. is close to S. australis Riera, Nunez, Brito, 2006, but differs from it in the comparatively shorter and more slender tail, small-er number of amphidial fovea turns, greater number of precloacal supplements in males and shape and structure of spic-ules. Dorylaimopsis intermedia sp. n. is morphologically closest to D. mediterranea Grimaldi-de Zio, 1968 and D. magellanense Chen, Vincx, 1968, but differs from both species in the longer outer labial setae and absence of precloacal supplements in males. D. brevispiculata sp. n. is similar to D. turneri Zhang, 1992 and D. coomansi Muthumbi, Soetaert, Vincx, 1977, but differs from both species in the shape of outer labial sensillae and absence of precloacal supplements in males. A pictorial key for determination of valid species in the genus Setosabatieria Rouville, 1903 is given.